A 2 and 5-Year Longitudinal Analysis of 671 Consecutive Patients Diagnosed with Unilateral Vestibular Schwannoma. Issue 6 (July 2022) - Tan, Neil C.-W.; Macfarlane, Robert; Donnelly, Neil; Mannion, Richard; Tysome, James R.; Jefferies, Sarah; Bance, Manohar; Axon, Patrick R.
Abstract : Objective: To analyse the 2 and 5-year outcomes of a cohort of patients with newly diagnosed vestibular schwannoma patients. Study Design: Longitudinal cohort study. Setting: Tertiary skull base referral unit. Patients: Six hundred and seventy-one consecutive patients referred to the Cambridge Skull Base Unit between 2005 and 2010. Main Outcome Measures: 1) Treatment outcomes, 2) hearing preservation, 3) facial nerve function, and 4) gross tumor control. Results: At initial diagnosis, 440/671(65.6%) of patients entered a watch, wait and rescan (WWR) pathway, 208/671 (31%) underwent primary microsurgical excision and 23/671 (3.4%) primary radiotherapy. Of patients who entered WWR, 144/440 (32.7%) exhibited tumor growth necessitating secondary intervention at a mean of 22.7 months; 67.4% had radiotherapy and 32.6% surgery. Radiotherapy was successful at achieving tumor control in 95% of cases. Primary surgery via the translabyrinthine route was performed in the majority of cases allowing for a radiologically clear surgical resection in 93% of cases. Conclusion: The Cambridge philosophy of treating the newly diagnosed vestibular schwannoma aims at preserving functional status where possible. In patients with small tumors it is recommended that they are placed on to a WWR pathway, of which 67.3% will not exhibit any growth by 5 years. If small tumors grow more than 2 mm by serial scanning, radiotherapy offers a high rate of tumor control. In patients with larger tumors more than 20 mm we would advocate microsurgical excision by the translabyrinthine route which offers excellent functional outcomes and gross tumor control.